Comparison Between Topical Sucralfate, Topical Platelet-Rich Plasma and Topical Ozonated Virgin Coconut Oil to Enhance Wound Healing in Diabetic Ulcer Mice model - Renni Yuniati; Matthew Brian Khrisna; Farmaditya Eka Putra; Kristophorus Heri Nugroho Hario Seno; Tri Nur Kristina (International Journal of Phytomedicine, 2021)
Diabetic ulcer is a serious complication of diabetes mellitus which can lead to further morbidity. Sucralfate, Platelet-rich plasma (PRP) and ozonated virgin coconut oil (VCO) has been shown to provide good clinical outcomes in chronic ulcer healing. This study compares the effectiveness of topical sucralfate, topical PRP and topical ozonated VCO therapy for diabetic ulcer treatment in Wistar mice by observing wound length and vascular endothelial growth factor (VEGF). Ninety Wistar mice with full-thickness ulcer model on the back were divided into 5 groups. Four groups of mice were receiving diabetic induction using streptozotocin injection and were allocated as topical sucralfate (TS), topical PRP (TP), and topical ozonated VCO (TO) group. The remaining diabetic-positive mice were allocated as the diabetic-positive control group (PC) which received standard therapy, and the other non-diabetic mice were allocated as the diabetic-negative control group (NC) which did not receive any therapy. Topical ozonated VCO enhances the wound healing process better with the greatest wound reduction area and highest VEGF expression compared to topical sucralfate and topical PRP. Topical ozonated VCO can potentially accelerate wound healing in diabetic ulcers better than topical sucralfate and topical PRP.